2021
DOI: 10.3390/jof7060436
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Anti-Cancer Activity of Secondary Metabolic Products from Marine Fungi

Abstract: The promising feature of the fungi from the marine environment as a source for anticancer agents belongs to the fungal ability to produce several compounds and enzymes which contribute effectively against the cancer cells growth. L-asparaginase acts by degrading the asparagine which is the main substance of cancer cells. Moreover, the compounds produced during the secondary metabolic process acts by changing the cell morphology and DNA fragmentation leading to apoptosis of the cancer cells. The current review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…293 The biosynthetic gene cluster tlxA-J for the hexacyclic meroterpenoids talaromyolides (isolated from Talaromyces purpureogenus) has been identied by heterologous expression, in vitro enzyme assays, and CRISPR-Cas9-based gene inactivation, revealing that the heterodimer of non-heme iron enzymes, TlxJ and TlxI, catalyses three steps of oxidation in the biosynthetic pathway. 294 Amongst the many reviews published on specic aspects of marine fungi were those on metabolites from endophytic species, 295 and on fungi isolated from sediment, 296 or from Sarcophyton species, 297 those based on compound type isolated (halogenated compounds 298 and bioactive alkaloids 299,300 ), and several based on metabolite activity type (anti-inammatory and anti-tumour, 301 anti-cancer 302 anti-cancer and anti-bacterial, 303 antibacterial, 304. and anti-microbial 305 ). Other reviews discussed marine fungi based on their geographical source (Antarctica 306 and Korea 307 ) or genus (Aspergillus, 308,309 Cladosporium, 310 Penicillium 311 ).…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…293 The biosynthetic gene cluster tlxA-J for the hexacyclic meroterpenoids talaromyolides (isolated from Talaromyces purpureogenus) has been identied by heterologous expression, in vitro enzyme assays, and CRISPR-Cas9-based gene inactivation, revealing that the heterodimer of non-heme iron enzymes, TlxJ and TlxI, catalyses three steps of oxidation in the biosynthetic pathway. 294 Amongst the many reviews published on specic aspects of marine fungi were those on metabolites from endophytic species, 295 and on fungi isolated from sediment, 296 or from Sarcophyton species, 297 those based on compound type isolated (halogenated compounds 298 and bioactive alkaloids 299,300 ), and several based on metabolite activity type (anti-inammatory and anti-tumour, 301 anti-cancer 302 anti-cancer and anti-bacterial, 303 antibacterial, 304. and anti-microbial 305 ). Other reviews discussed marine fungi based on their geographical source (Antarctica 306 and Korea 307 ) or genus (Aspergillus, 308,309 Cladosporium, 310 Penicillium 311 ).…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…What is noteworthy is that satratoxin F ( 364 ) as a known lactone displayed excellent cytotoxic activities against five human cancer cell lines (MDA-MB-231, C4-2B, MGC803, MDA-MB-468, and A549) with EC 50 values less than 39 nM. A previous review indicated that fungi was regarded as the best candidate as a source of anticancer agents [ 186 ]. In addition, another alkaloid, aflaquinolone D ( 111 ), exhibited notable antifouling activity with EC 50 values of 2.8 nM.…”
Section: Comprehensive Overview and Conclusionmentioning
confidence: 99%
“…Over the last decades, colored secondary metabolites have been investigated regarding their antitumorigenic efficacy [ 27 , 28 ]. It has been proven that they interfere with various cell signaling pathways, such as the cell cycle pathway, survival, and cell death [ 29 , 30 ].…”
Section: Plant Colored Secondary Metabolites Of Interest For Oncology...mentioning
confidence: 99%